The Study of Maqashidi Sharia Toward Maduresse Traditional Inheritance by Using System Approach - Mohammad Hipni (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
In traditional societies such as Maduresse who carry out religious teaching strongly, women in certain contexts are generally positioned in the lower position than men. However, in the cultural context of Maduresse inheritance, women are on the equal footing with men. Even, parents give more priority on the legacy to their daughters. The purpose of this study is to understand the phenomenon of the women position in traditional Maduresse legacy by using maqashid sharia particularly the system approach. The use of system approach aims to explain parts that influence the position of women in Maduresse traditional inheritance system and determine the legislation ratio on the legal phenomenon. This research discovers that women in Madurese society are considered not only as passive family members, but also as a symbol of honor and sustainability in Madurese family. These arguments make Maduresse’s understanding on the inheritance verses more comprehensive. Therefore, women are positioned equal with men for the legacy distribution in Madura traditional inheritance (Pada masyarakat tradisional seperti Madura dengan karakter keras memegang teguh agama, wanita pada konteks tertentu diletakkan dalam posisi yang lebih rendah dari pada laki-laki. Namun, dalam konteks kewarisan adat Madura, wanita diposisikan setara dengan kaum laki-laki. Bahkan, orang tua memberikan prioritas lebih atas bagian waris anak perempuannya. Penelitian ini bertujuan memahami fenomena kedudukan wanita dalam waris adat Madura dengan menggunakan maqãshid syarĩah khususnya pendekan sistem. Analisis sistem ini diharapkan mampu menjelaskan bagian-bagian yang memengaruhi kedudukan wanita dalam sistem waris adat Madura dan mengetahui ratio legis dari fenomena hukum tersebut. Penelitian ini menghasilkan temuan bahwa wanita dalam masyarakat Madura dianggap tidak hanya sebagai anggota keluarga pasif, namun sebagai simbol kehormatan dan simbol keberlangsungan keluarga masyarakat Madura. Pandangan yang demikian membuat pemahaman terhadap ayat waris lebih komprehensif. Oleh karena itu, wanita diposisikan setara dengan laki-laki dalam pembagian waris adat yang dipraktikkan dalam adat masyarakat Madura)